Formation and stability of emulsions stabilised by Yucca saponin extract. (27th December 2017) - Ralla, Theo; Salminen, Hanna; Tuosto, Jessica; Weiss, Jochen
Summary: Yucca saponin extract containing steroidal saponins was examined for its interfacial and emulsifying properties. For this purpose, we produced oil‐in‐water emulsions and tested their stability against environmental stresses (pH, ionic strength, heating and freeze‐thawing). Yucca saponin extract was highly surface‐active and formed negatively charged submicron‐sized emulsions at low surfactant‐to‐oil ratio. The emulsions were stable at pH 5–9 and showed only minor increase in droplet size when heated up to 90 °C. Our results indicate Yucca saponin extract as a new potential natural surfactant that may be used to replace synthetic surfactants in the food and beverage industry for selected applications. Abstract : Formation of emulsions stabilised by Yucca saponin extract.